Penggunaan Talking Stick untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris Siswa Kelas III A UPT SDN Sungguminasa V - R, Mutahharah; Mariati, Mariati; Idawati, Idawati (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
This research aims to determine the effect of using talking sticks to improve students' mastery of English vocabulary. This research uses the classroom action research (PTK) method using 2 cycles. The subjects in this research were 32 students. There was a significant difference in Cycle I and Cycle II with the highest score in Cycle I being 60 and in Cycle II the highest score was 90. The data collection technique used test instruments. The results of the research show that there is an influence of using talking sticks to improve students' mastery of English vocabulary. The average score from cycle I was 37 and the lowest score was 20 and in Cycle II the average score was 84 and the lowest score was 70. The English vocabulary mastery of class III A students at SDN Sungguminasa V has the influence of using talking sticks to improve vocabulary mastery. students' English.